First record of Osmylidae (Neuroptera) from Colombia and description of two new species of Isostenosmylus Krüger, 1913 - Ardila-Camacho, Adrian; Noriega, Jorge Ari (Zootaxa, 2014)
The family Osmylidae is recorded for the first time in Colombia, extending its known distribution range to the north of South America in the northern Andes. Two new species of the genus Isostenosmylus Krüger, 1913, I. contrerasi n. sp. and I. septemtrionalandinus n. sp. and one morphospecies distributed along the eastern cordillera in the departments of Cundinamarca, Huila, and Norte de Santander are described and illustrated. A key to species of the genus Isostenosmylus, as well as a list of South American species of Osmylidae is included.